Vangl as a Master Scaffold for Wnt/Planar Cell Polarity Signaling in Development and Disease - Dreyer, Courtney A.; VanderVorst, Kacey; Carraway, Kermit L. (Frontiers in Cell and Developmental Biology, 2022)
The establishment of polarity within tissues and dynamic cellular morphogenetic events are features common to both developing and adult tissues, and breakdown of these programs is associated with diverse human diseases. Wnt/Planar cell polarity (Wnt/PCP) signaling, a branch of non-canonical Wnt signaling, is critical to the establishment and maintenance of polarity in epithelial tissues as well as cell motility events critical to proper embryonic development. In epithelial tissues, Wnt/PCP-mediated planar polarity relies upon the asymmetric distribution of core proteins to establish polarity, but the requirement for this distribution in Wnt/PCP-mediated cell motility remains unclear. However, in both polarized tissues and migratory cells, the Wnt/PCP-specific transmembrane protein Vangl is required and appears to serve as a scaffold upon which the core pathway components as well as positive and negative regulators of Wnt/PCP signaling assemble. The current literature suggests that the multiple interaction domains of Vangl allow for the binding of diverse signaling partners for the establishment of context- and tissue-specific complexes. In this review we discuss the role of Vangl as a master scaffold for Wnt/PCP signaling in epithelial tissue polarity and cellular motility events in developing and adult tissues, and address how these programs are dysregulated in human disease.